KOMPOSISI BOTANI DAN PRODUKSI BIOMASSA TANAMAN PAKAN TERNAK DI DESA PONGKOR KABUTAPEN MANGGARAI - Hilarius Yosef Sikone; Erminia Pereira Dos Santos; Yohanes Monterio Kantur; Serlin Anjelita Djami; Albertus Agung; Redemta Hernitania Oktolanung (Jurnal Agriovet, 2024)
This study aims to identify the botany of animal feed crops and calculate the biomass production of animal feed crops in the field. The research was conducted in Pongkor Village, Satar Mese District, Manggarai Regency in April-May 2024. The methods used are survey methods as well as measurements and direct observations in the field. Forage production measurements were carried out using the "Actual Weight Estimate" method. The variables of this study are the identification of feed crops, dry weight of type, dry weight ratio and biomass production. All primary data taken were analyzed by tabulation or calculated to obtain the percentage of botanical composition and average forage production of forage. Meanwhile, secondary data is analyzed according to the needs of writing research results. The results showed that the botanical composition of animal feed plants in Pongkor Village consisted of Chrysopogon Aciculatus, Lantana Camara L., Uellia Blechum L., Stachytapheta Jamaicensis and Cuphea Elliptica Koehne. The highest biomass production was Chrysopogon Aciculatus with a biomass production of 7.9 tons/ha±0.12 followed by Stachytapheta Jamaicensis with a biomass production of 7.2 tons/ha±0.50 while the least biomass production was in the Ruellia Blechum L. plant with a biomass production of only 2.4 tons/ha±0.64.